Development of Neuroscience-Based Chemistry Teaching Module on Green Chemistry Material - Anggraini, Henny; Sofiyanita, Sofiyanita (Journal of Natural Science and Integration, 2025)
This study aims to (1) develop a neuroscience-based chemistry teaching module on green chemistry topics, and (2) produce a valid and practical module for use in classroom instruction. The research employed a Research and Development (R&D) approach, adopting the Thiagarajan 4-D model, comprising four stages: Define, Design, Develop, and Disseminate. The study was conducted up to the Development stage, involving module validation and practicality testing. Research activities took place at Cendana High School, Pekanbaru, with participants including material experts, media experts, a chemistry teacher, and Class X-1 students. Data were collected through interviews, validity and practicality questionnaires, and student response surveys, utilizing a Likert scale. The analysis combined qualitative descriptive methods—capturing feedback, criticisms, and suggestions—with quantitative descriptive techniques to interpret questionnaire data. Results showed that the module’s content validity, assessed by material experts, reached 85.29%, categorized as very valid, while media expert validation yielded 81.25%, also very valid. Practicality tests indicated that chemistry teachers rated the module at 90% (very practical), and student responses achieved 82.96% (very practical). These findings suggest that the neuroscience-based chemistry teaching module on green chemistry is both valid and highly practical, making it suitable for enhancing chemistry instruction. Keywords: teaching module, neuroscience, green chemistry